THE ROLE OF THE MOTHER IN THE FAMILY TO PREVENT CHILDREN'S CARIES IN THE SUNGAI JAWI - Mahmiyah, Erma; Setiawaty Ningsih, Neny; Maryani, Yeni; Fathiah, Fathiah; Suryana, Budi (JURNAL TERAPIS GIGI DAN MULUT, 2024)
Caries is a dental problem that is most often found in elementary school-age children, dental caries experienced by children is closely related to the role of parents, the role of the mother is so important in maintaining dental and oral health in schoolage children. The prevalence of caries in the 5-9 years age group was 92.6% and in the 10-14 years age group the caries prevalence was 73.4%. This study aims to determine the role of the mother in the family to prevent child caries and DMF-T rate. The research design used in this study was cross-sectional quantitative analysis using a survey method with a total sample of 70 people using a total sampling technique. The results of this study show that the role of the mother with the DMF-T rate shows that the mother has a good role with a moderate caries rate of 17 respondents with a percentage (24%). The role of the mother is classified as good because the mother fully facilitates the child's needs for the importance of maintaining healthy teeth and mouth. From this study it can be concluded that family support, in this case the role of the mother, is very important for the DMF-T rate of elementary school children.